(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Veggie fish longganisa is a Filipino sausage made with fish and vegetables instead of pork or chicken. It is typically made of galunggong and tilapia fish with mixed vegetables. It is prepared similar to how other Filipino longganisas are prepared and is marketed as a healthier alternative. The researchers used galunggong and tilapia because they are healthier than pork and chicken. This study used a descriptive research method wherein different guided instruments, such as survey questionnaires, SWOT analysis, 4Ps, and financial aspects, were used. The main objective of implementing marketing strategies by using SWOT analysis was to assess internal and external factors, as well as current and future potential customers. The business used a survey questionnaire that was sent to 100 respondents near the location of the establishment. Researchers used 4Ps to identify their perceptions about the product. It also utilized financial statements to see if the business will grow, is productive, and feasible. The results of this study stated that the viability of the business prospecting to a great market in the local sausage industry is effective and efficient. The respondents of this study were self-employed, employed, unemployed, and students. Employed respondents were the majority of the respondents who are willing to patronize the product in terms of pricing, demographics, and promotions. The financial statement determined it as remunerative to operate and generate enough revenue and investments. The business effectuates a visible return of investment of 5% circulation every year. If the run of the business is well-maintained and managed, the business will continue to surpass profit and success. The study found out the quality of the product should be reassured, and business offerings and promos should continuously improve to meet customer satisfaction. Every employee must be treated as a family to have a better working environment. Owners should also know the best platform to forecast products. The expenses of the raw materials should be consolidated to minimize the production cost.